Assessing the risk of climate change to select agricultural systems in the world’s most vulnerable regions - Gosling, Amanda; Ng'ang'a, Kevin; Gichuki, Leah (2022)
The Climate Risk Planning and Managing Tool for Development Programmes in the Agriculture and Food Sector (CRISP) project, funded by the Federal Ministry for Economic Cooperation and Development (BMZ)/ Deutsche Gesellschaft für Internationale Zusammenarbeit GmbH (GIZ), aims to address the shortfall in climate risk screening tools. The project is a collaboration between Eurac Research (Italy) and the Alliance of Bioversity and the International Centre for Tropical Agriculture (CIAT). The purpose of the CRISP project is to develop a freely available, quick and simple to use, interactive web-based tool for use by agricultural and rural development project planners and managers. The project is designed to help strengthen national and international agricultural and rural development funding proposals and projects, by making explicit the contribution of these towards adaptation targets as outlined in countries’ Nationally Determined Contributions (NDCs) and National Adaptation Plans (NAPs). This working paper outlines the development of the knowledge base for informing the CRISP tool. It describes the concept of climate risk in accordance with the Intergovernmental Panel on Climate Change (IPCC) and how it applies to agriculture. It then introduces impact chains which are useful tools for understanding risk in a system, and the methodology used to research, develop and validate impact chains for agricultural systems in five of the world’s developing regions. The report concludes with descriptions of the agricultural systems, summaries of the associated impact chains and an overview of the climate risks.